The Cambridge history of Greek and Roman political thought - edited by Christopher Rowe (Cambridge Cambridge University Press, 2005)
Beginning with Homer and ending in late antiquity with Christian and pagan reflections on divine and human order, this volume is the first general and comprehensive treatment of Rome ever to be published in English. Its international team of distinguished scholars includes historians of law, politics, culture and religion, as well as philosophers. The volume will long remain an accessible and authoritative guide to Greek and Roman thinking about government and community. Cambridge Histories Online
Includes bibliographical references (p. 672-728) and index.
Keywords: Political science--Greece--History.